Grip it and rip it: Structural mechanisms of DNA helicase substrate binding and unwinding - Bhattacharyya, Basudeb (Protein Sci, 2014)
Maintenance and faithful transmission of genomic information depends on the efficient execution of numerous DNA replication, recombination, and repair pathways. Many of the enzymes that catalyze steps within these pathways require access to sequence information that is buried in the interior of the DNA double helix, which makes DNA unwinding an essential cellular reaction. The unwinding process is mediated by specialized molecular motors called DNA helicases that couple the chemical energy derived from nucleoside triphosphate hydrolysis to the otherwise non-spontaneous unwinding reaction. An impressive number of high-resolution helicase structures are now available that, together with equally important mechanistic studies, have begun to define the features that allow this class of enzymes to function as molecular motors. In this review, we explore the structural features within DNA helicases that are used to bind and unwind DNA. We focus in particular on “aromatic-rich loops” that allow some helicases to couple single-stranded DNA binding to ATP hydrolysis and “wedge/pin” elements that provide mechanical tools for DNA strand separation when connected to translocating motor domains.